Analysis of The Effectiveness of Monetary Policy in Promoting Inclusive Economic Growth in Indonesia: A Comparative Study For The Period 2015-2025 - Zulfina Tsanin Mayyadah; Karsinah Karsinah (Dinasti International Journal of Education Management And Social Science, 2025)
This study analyzes the effectiveness of monetary policy in promoting inclusive economic growth in Indonesia during the 2015-2025 period. Global economic dynamics and structural transformation of monetary policy through the P2SK Law have shifted Bank Indonesia's paradigm from stability-focused to balancing stability and inclusivity. Using a qualitative approach through literature studies and content analysis, the research identifies three phases of monetary policy: Stabilization Phase (2015-2019), Pandemic Response Phase (2020-2022), and Structural Transformation Phase (2023-2025). Results indicate varying effectiveness across policy instruments, with differentiated reserve requirements and payment system digitalization positively contributing to inclusivity. Determinants of effectiveness include institutional factors, economic structure, external factors, and financial-digital infrastructure that interact to create regional disparities. Monetary policy reformulation is necessary through the development of multi-dimensional evaluation metrics, strengthening regional policy coordination, differentiated instrument innovation, and accelerating digital transformation of the financial system to achieve more inclusive economic growth.